2021
DOI: 10.1007/s00213-021-05955-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent cocaine induced persistent negative affect in female rats exposed to early-life stress

Abstract: Rationale The combination of several risk factors (sex, a prior underlying psychiatric condition, or early drug initiation) could induce the emergence of negative affect during cocaine abstinence and increase the risk of developing addiction. However, most prior preclinical studies have been centered in male rodents, traditionally excluding females from these analyses. Objectives To ascertain the behavioral and neurochemical consequences of adolescent coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…However, this lack of behavioral impact is accompanied by changes in neurochemical markers in the hippocampus (i.e., increased pro-apoptotic FADD [ 71 ]), a brain region particularly responsive to stress, suggesting a negative impact induced by this procedure. Moreover, the combination of maternal separation with a different stressor (i.e., drug administration during adolescence) induced negative affect [ 71 , 72 ], in line with the literature reporting the “two-hit” hypothesis in the development of neuropsychiatric illnesses (a combination of two or more major disruptions are needed at specific time points during development). Moreover, it is important to remember that the forced-swim test is a good test to measure antidepressant-like responses, but not necessarily to phenotype a depressive-like response (reviewed by [ 73 ]).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, this lack of behavioral impact is accompanied by changes in neurochemical markers in the hippocampus (i.e., increased pro-apoptotic FADD [ 71 ]), a brain region particularly responsive to stress, suggesting a negative impact induced by this procedure. Moreover, the combination of maternal separation with a different stressor (i.e., drug administration during adolescence) induced negative affect [ 71 , 72 ], in line with the literature reporting the “two-hit” hypothesis in the development of neuropsychiatric illnesses (a combination of two or more major disruptions are needed at specific time points during development). Moreover, it is important to remember that the forced-swim test is a good test to measure antidepressant-like responses, but not necessarily to phenotype a depressive-like response (reviewed by [ 73 ]).…”
Section: Discussionsupporting
confidence: 57%
“…To model a more robust depressive-like phenotype we would have needed other preclinical approaches that include more aggressive and/or prolonged procedures that might have even interfered with the timing of the adolescent treatment (e.g., [ 19 ]). Therefore, early-life stress modeled with maternal separation, although failed to show baseline changes in affective-like behavior with the tests performed (as previously described in [ 71 , 72 ]), proved differences in the effectiveness of the selected drug treatments, both in adolescence and adulthood, presenting itself as a good platform in which to explore novel antidepressant options for adolescence with a sex perspective.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since no behavioral differences were observed between both groups (data not shown), rats were combined in a group of 20 rats in which to evaluate the impact of adult cocaine exposure with no prior history of cocaine on the emergence of psychomotor sensitization. This selected cocaine regimen was previously shown to induce psychomotor sensitization in adult outbred ( 42 ) and bHR rats ( 43 ), and to induce long-term behavioral changes [e.g., ( 44 47 )] when given at this time-window during early-mid adolescence.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescent experience of drug abuse increases risk of developing psychiatric disorders that even persists into adulthood, which is a big public heath concern worldwide (3)(4)(5)(6)(7)(8). Previously, we found that adolescent cocaine exposure (ACE) increased anxiety-like behaviors in mice of adulthood (9,10), which is generally believed as critical factor for driving relapse to drugs in later life (11,12).…”
Section: Introductionmentioning
confidence: 99%